Being (almost) invisible: Victims of crime in the Italian juvenile criminal justice system - Vezzadini Susanna (Temida)
From 2008 to 2013 the author has been a Special Judge in the Juvenile Criminal Court of the Emilia Romagna Region. From that privileged perspective, it was possible to observe the dynamics of how victims of underage offenders were considered before the law, no differences if they are adults or minors, too. The reflections presented will first consider EU and UN provision on victims of crime; then, the normative framework supporting the Italian criminal juvenile justice system will be considered by an examining of the difficulties victims meet in that peculiar context. The implementation of juvenile criminal law shows the paradox victims of crime have to cope with. The Juvenile Criminal Court in Bologna recently started to promote a wide use of restorative justice measures as an attempt to correct the unfair consequences in the application of law, with judicial discretion interpreted as an instrument to favour victims’ harm recognition and to protect their dignity as persons.